Tingkat Partisipasi Masyarakat dan Keberlanjutan Pengelolaan Bank Sampah di Desa Tuwel, Kecamatan Bojong, Kabupaten Tegal (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2020)
Waste banks as a place for sorting and collecting waste that can be recycled and / or reused which has economic value but is oriented to environmental sustainability. Waste banks require community participation in their implementation so that they are expected to provide benefits. These benefits can make the waste bank program experience sustainability in carrying out waste management activities. The purpose of this study is to (1) analyze the level of community participation in Waste Banks; (2) analyze the factors related to the level of participation; and (3) analyze the relationship between the level of community participation and the level of sustainability of the waste bank program. Data were collected using questionnaire instruments and analyzed using Rank Spearman correlation test. The results of the study involving 50 respondents indicated that the factors related to the level of community participation were the level of non-formal education, government support, procurement of facilities and infrastructure, and the acquisition of incentives. The level of community participation is significantly related to the sustainability of waste management activities through waste banks.Â